English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I don't understand how to simplify 2x - 2y = 2 to get y= x - 1
HELP!!!

2007-04-25 09:38:07 · 7 answers · asked by animal_luver313 1 in Science & Mathematics Mathematics

i need Y on the left side!!!

2007-04-25 09:46:42 · update #1

7 answers

2x - 2y = 2

Divide through by 2

x - y = 1

Transpose - x on both sides of the equation

x - y - x = - x + 1

- y = - x + 1

Multiply -1 on both sides of the equation

-1(- y) = -1( - x) + (- 1)(1)

- ( - y) = - ( - x) + (- 1

y = x - 1

2007-04-25 10:17:52 · answer #1 · answered by SAMUEL D 7 · 1 0

2x - 2y = 2
Shift 2y to right hand side: 2x = 2 + 2y
Shift 2 to left hand side: 2x - 2 = 2y
Divide throughout by 2: x - 1 = y
Which is equivalent of y = x - 1.

2007-04-25 16:42:46 · answer #2 · answered by Yuehan Z 1 · 0 0

Step 1: Divide the each term in the equation by 2 (performing any mathematical operation on both sides of an equation maintains a valid equation). This gives:
x-y=1
Step 2: Solve for y by subtracting x from both sides of the equation. This gives:
-y=1-x
Step3: multiply both sides of the equation by -1 (which changes all of the signs) This gives the final answer:
y= -1+x or x-1

2007-04-25 16:55:51 · answer #3 · answered by Leonard B 1 · 0 0

Divide the whole problem by 2.

Divide by 2 on the left and 2 on the right.

You get x - y = 1

add y to each side -> x = y+1

subtract 1 from each side -> x-1 = y

2007-04-25 16:45:41 · answer #4 · answered by csucdartgirl 7 · 0 0

2x - 2y = 1
x - y = 1 [divide both sides by 2]
x = 1 + y [add y to both sides]
x - 1 = y [subtract 1 from both sides]

2007-04-25 16:42:41 · answer #5 · answered by Crystal 3 · 0 0

i understand why you are confused, the steps are listed below i hope this is helping

2x - 2y = 2
subtract 2x from both sides
now you have: -2y = -2x + 2
divide the whaole equasion by -2
now you have y = x - 1

2007-04-25 16:45:53 · answer #6 · answered by Anonymous · 0 0

Sometimes you just have to try something and see how it works.

Surely you must see that every term has a 2 in it.

Divide throughout by 2.
x - y = 1
Then carry across the y
x - 1 = y

2007-04-25 16:43:42 · answer #7 · answered by Dr D 7 · 0 0

fedest.com, questions and answers